2014
DOI: 10.1179/1743284714y.0000000536
|View full text |Cite
|
Sign up to set email alerts
|

Secondary hardened bainite

Abstract: The effect of Mo additions on the development of bainitic ferrite in hot rolled low carbon (0?05 wt-%C) Nb containing steel strips has been studied. The steel strips were fabricated by a combined process of controlled rolling and accelerated cooling. Microstructural characterisation and mechanical testing for the corresponding strips were investigated. The results indicated that a small amount of Mo addition (0?1-0?3 wt-%) causes the production of a high volume fraction of bainite, which undergoes significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
4
19
0
Order By: Relevance
“…The following misorientation profiles show the accumulated point to origin The present pole figure investigation supports the view point of the paper [28] and disagrees on that of the paper [19], which claims that the spread is caused by a trace [29].…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…The following misorientation profiles show the accumulated point to origin The present pole figure investigation supports the view point of the paper [28] and disagrees on that of the paper [19], which claims that the spread is caused by a trace [29].…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…Therefore, strength contributed by nano-sized precipitates is almost equal with improvement of yield strength for samples after tempering in the present work. In addition, Previous studies [24][25][26] have suggested that MC-type nano-scale precipitates formed in ferrite always have the coherence relationship with surrounding ferrite matrix. Precipitation strengthening can be commonly explained by the Ashby-Orowan mechanism, as given by the following Eq.…”
Section: Nano-sized Precipitates and The Strengthening Effectmentioning
confidence: 97%
“…Huang and Yang [24] studied the evolution of dislocation for low carbon micro-alloying steel on tempering. Their results have revealed that the decrease in the dislocation density in granular bainitic structure after tempering at 600°C even for 8 h is extremely small.…”
Section: Nano-sized Precipitates and The Strengthening Effectmentioning
confidence: 99%
“…Colder finishing conditions promoting bainite formation largely prevent niobium precipitation. Secondary heat treatment such as tempering, however, allows nearly complete precipitation [23]. niobium precipitation.…”
Section: Introductionmentioning
confidence: 99%